001.1 Evolution and spread of antibiotic-resistant gonorrhoea. (13th September 2015) - Fingerhuth, SM; Bonhoeffer, S; Low, N; Althaus, CL
Abstract : Introduction: Neisseria gonorrhoeae has developed resistance to all classes of antimicrobials that have been used to treat it and strains that are resistant to multiple classes of antimicrobials have evolved. Only one antimicrobial (ceftriaxone) can now be used for empirical treatment in many countries. Hence, it is important to understand the dynamics and drivers of resistance evolution. Methods: First, we estimated rates of resistance evolution from antimicrobial resistance surveillance data from the USA and from England and Wales for heterosexual men (HetM) and men who have sex with men (MSM). Second, we developed dynamic transmission models to reconstruct the observed dynamics of N. gonorrhoeae transmission and resistance evolution in both HetM and MSM. Results: We found that resistance to ciprofloxacin and cefixime initially spreads exponentially at rates between 0.2 and 2.4 per year. These rates suggest that the proportion of resistant strains doubles every 3 to 35 months. We found lower rates of spread in HetM (0.2 to 0.8) compared with MSM (0.9 to 2.4). The models show that the treatment rate is the driving force for the spread of resistance. Conclusion: There is a trade-off in optimising the treatment rate to provide individual patient care to all those who are infected and to keep the spread of resistance as low as possible. These findings have implications for developing antimicrobial treatment strategies and point-of-care tests to detect resistance. Disclosure of interest statement: This study received support from the RaDAR-Go (Rapid Diagnosis of Antimicrobial Resistance in Gonorrhoea) project, funded by SwissTransMed and from the Swiss National Science Foundation. No pharmaceutical grants were received for the conduct of this study.